2015
DOI: 10.5713/ajas.15.0445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Feeding Systems on Production Performance, Rumen Fermentation and Rumen Digesta Particle Structure of Beef Cattle

Abstract: The effects of three different feeding systems on beef cattle production performance, rumen fermentation, and rumen digesta particle structure were investigated by using 18 Limousin (steers) with a similar body weight (575±10 kg) in a 80-d experiment. The animals were equally and randomly divided into three treatment groups, namely, total mixed ration group (cattle fed TMR), SI1 group (cattle fed concentrate firstly then roughage), and SI2 group (cattle fed roughage firstly then concentrate). The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 19 publications
2
18
1
Order By: Relevance
“…The high number of unclassified sequences detected in this study has also been reported by other groups ( Creevey et al, 2014 ; Liu et al, 2016 ) and is not surprising given the large percentage of rumen bacteria that still remain unculturable. The generation of a reference set of rumen microbial genome sequences by initiatives such as the Hungate 1000 should facilitate more accurate classification in the future ( Creevey et al, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…The high number of unclassified sequences detected in this study has also been reported by other groups ( Creevey et al, 2014 ; Liu et al, 2016 ) and is not surprising given the large percentage of rumen bacteria that still remain unculturable. The generation of a reference set of rumen microbial genome sequences by initiatives such as the Hungate 1000 should facilitate more accurate classification in the future ( Creevey et al, 2014 ).…”
Section: Discussionsupporting
confidence: 89%
“…According to a survey by Heinrichs et al [ 38 ], only 7.1% of the particles in TMR were greater than 19 mm versus 16–18% for various forages, which is consistent with our results of 54 and 181 g/kg DM that is 5.4% and 18.1% for TMR and SF, respectively. Liu et al [ 39 ] reported that TMR feeding had a greater proportion of ruminal contents with particle size < 1.18 mm, which is the critical size for particles to pass the rumen [ 40 ]. Although reducing forage particle size during the TMR mixing process usually results in reduced rumen solid retention time, the effects on DMI and digestibility remain less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive amount of long fibres could limit dry matter intake and digestibility, as a short particle size decreases chewing activity and results in a decline of saliva production and rumen pH [18] . Especially regarding this concern, several studies have been conducted on dairy cows [8,19,20] , beef cattle [7,21] and goats [22] .…”
Section: Discussionmentioning
confidence: 99%